The Authority of Judges to Independently Determine the Amount of State Financial Losses in Verdicts on Corruption Cases - KMS Herman; Anesia, Nila; Rukmana, Indra Jaya; Amelia, Rini Fitri Octa; Marpaung, Raja Robert (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Law enforcement in corruption cases in Indonesia often faces challenges related to proving the element of state financial loss. One of the issues that arises is the authority of judges to independently determine the amount of state loss without relying on an official audit by state audit institutions such as the Audit Board of Indonesia (BPK) or the Financial and Development Supervisory Agency (BPKP). This study employs a normative juridical research method using a statute approach and an analytical approach to examine the legal basis, judicial practices, and implications of such authority. The findings indicate that although Article 183 of the Indonesian Criminal Procedure Code (KUHAP) grants judges the authority to decide based on at least two valid pieces of evidence, the absence of an official audit can lead to legal uncertainty, the risk of judicial error, and violations of the defendant’s right to a fair trial. Therefore, harmonization between regulations and judicial practice is necessary to ensure legal certainty, protection of human rights, and the effectiveness of corruption eradication.